A Simple Representation of Plant Water Storage Effects in Coupled Soil Water Flow and Transpiration Stream Modeling. Issue 5 (11th May 2017) - Vogel, Tomas; Votrubova, Jana; Dohnal, Michal; Dusek, Jaromir
Abstract : Core Ideas: A previous soil water flow model was extended to allow simulation of transient plant water storage. Comparison with measured Norway spruce sap flow data indicates improved model performance. The proposed algorithm can be easily incorporated into existing soil water flow models. When describing the movement of water in a variably saturated plant root zone, most existing hydrological models use the assumption of quasi‐steady‐state flow to relate root water uptake to canopy transpiration, thereby neglecting the effect of changing plant water storage. This approach is known to be problematic, especially when considering relatively large volumes of water stored in the tissues of tall trees. We propose a simple algorithm, based on the concept of whole‐plant hydraulic capacitance, to deal with the problem. The algorithm is implemented in a one‐dimensional soil water flow model involving vertically distributed macroscopic root water uptake. In this study, the proposed transient storage approach was compared with the quasi‐steady‐state approach. Both approaches were used to simulate soil water flow and diurnal variations of transpiration at a forest site covered with Norway spruce [ Picea abies (L.) H. Karst.]. The key parameter of the transient storage approach, the plant hydraulic capacitance, is estimated by comparing the variations in the potential transpiration rate, derived from micrometeorological measurements, with observed sap flow intensities. The application of the proposed algorithm leads to more realistic predictions of root water uptake rates at the site of interest. The inclusion of the plant water storage effects improved the ability of the model to capture the anticipated diurnal variations in actual transpiration rates. The algorithm can be easily implemented into existing soil water flow models and used to simulate transpiration stream responses to varying atmospheric and soil moisture conditions including isohydric and partly also anisohydric plant responses to drought stress.